2009
DOI: 10.1111/j.1755-9294.2009.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of decreased expression of CD56 protein in papillary carcinoma of the thyroid gland

Abstract: Background and aims:Precise pathological diagnosis is essential for optimal treatment of thyroid tumors. Ancillary diagnostic markers may be helpful in some cases. The purpose of this study was to compare and evaluate the diagnostic value of CD56, cytokeratin 19 (CK19), and galectin-3 immunohistochemical stainings in distinguishing between papillary carcinoma (PC) and other thyroid malignancies and benign lesions. Methods: The expressions of the three markers were evaluated in PC (n = 67), follicular carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 18 publications
6
40
2
Order By: Relevance
“…[26] Many previous studies reported high CD56 expression in normal thyroid tissue and benign thyroid follicular lesions as Follicular Adenomas and Nodular Hyperplasias. [4,7,27,28] In our study, moderate to strong staining intensity was seen in 41% cases of Benign lesions and negative expression in 29% cases. [26] and Shahebrahimi et al [29] Atti et al reported a high positive CD56 expression in normal thyroid tissue compared to PC cases.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…[26] Many previous studies reported high CD56 expression in normal thyroid tissue and benign thyroid follicular lesions as Follicular Adenomas and Nodular Hyperplasias. [4,7,27,28] In our study, moderate to strong staining intensity was seen in 41% cases of Benign lesions and negative expression in 29% cases. [26] and Shahebrahimi et al [29] Atti et al reported a high positive CD56 expression in normal thyroid tissue compared to PC cases.…”
Section: Discussionsupporting
confidence: 55%
“…[26] Shahebrahimi et al observed that CD56 was expressed in 93% of all Benign lesions, while it was only found in 5% of Malignant thyroid lesions (PC). [29] Similarly, previous studies by Demellawy et al, [4,28] Park et al, [27] and Shin et al [7] reported that negative CD56 expression in all or most of their studied PC cases and also observed that CD56 expression was more reduced in Papillary Carcinomas in respect to Follicular Carcinomas and Follicular Adenomas.…”
Section: Discussionmentioning
confidence: 59%
“…According to Park et al [22], strong and complete membranous expression with or without cytoplasmic staining of the cells qualified the case as positive for CD56.…”
Section: Interpretation Of Immnohistochemical Staining Of Cd56mentioning
confidence: 99%
“…Strong and complete membranous expression with or without cytoplasmic staining qualified the case as positive for CD56. 6,7 Low or absent expression of CD56 is noted in papillary carcinoma of thyroid. 7 In the NCDB (National Cancer Data Base, USA) study, the 10 year relative survival rates for patients with papillary and follicular carcinoma were 93% and 85%, respectively.…”
Section: Cd56mentioning
confidence: 99%
“…5 This is due to advances in medical surveillance of impalpable nodules and increased emphasis on ancillary tests. 6 Such increase also reflects a minor component of over diagnosis of PTC. It is clear that some cases do raise controversy as being PTC or non PTC.…”
Section: Introductionmentioning
confidence: 99%